PENGARUH KEPERCAYAAN DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PELANGGAN DI MARKETPLACE SHOPEE - Achmad Jalil; Arief Syah Safrianto (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2023)
This study aims to analyze the effect of customer trust and product quality on purchasing decisions on the Shopee marketplace. This research uses a causality approach between customer trust and product quality on purchasing decisions on the Shopee marketplace. The object of this research was conducted at Krisnadwipayana University students, the research location is located at Jalan. UNKRIS Jatiwaringin, Pondok Gede. This study used a sample of 100 students at the Student Organization of the Faculty of Economics, Krisnadwipayana University. The results of the study show that customer trust and product quality can have a positive and significant influence on purchasing decisions on the Shopee marketplace.